Structural phase transitions in thin convection at dependence of viscosity on temperature - Gushchin, I.V.; Kuklin, V.M. (Вопросы атомной науки и техники, 2018)
Conditions for a second-order phase transition in a thin liquid layer with poorly conductive boundaries under
conditions of dependence of viscosity on temperature are considered. It is shown that, when the dependence is weak,
the shaft system of toroidal vortices develops first, and then a field of square convective cells is being formed. If the
viscosity dependence on temperature is strong, even for the system described by Proctor-Sivashnsky equations, transitions from the shaft structure to hexagonal convection cells are possible. Розглянуто умови для фазового переходу другого роду в тонкому шарі рідини з границями, що погано
проводять тепло, в умовах залежності в'язкості від температури. Показано, що при слабкій залежності розвивається спочатку валікова система тороїдальних вихорів, а потім формується поле квадратних конвективних осередків. Якщо залежність в'язкості від температури сильна, навіть для системи, що описується рівнянням Проктора-Сівашинського, можливі переходи від валікової структури до шестигранних конвективних
осередків. Рассмотрены условия для фазового перехода второго рода в тонком слое жидкости с плохо проводящими
тепло границами в условиях зависимости вязкости от температуры. Показано, что при слабой зависимости
развивается сначала валиковая система тороидальных вихрей, а затем формируется поле квадратных конвективных ячеек. Если зависимость вязкости от температуры сильная, даже для системы, описываемой
уравненими Проктора-Сивашинского, возможны переходы от валиковой структуры к шестигранным конвективным ячейкам.